The Unwanted Heritage of Prefabricated Wartime Air Raid Shelters—Underground Space Regeneration Feasibility for Urban Agriculture to Enhance Neighbourhood Community Engagement - Paweł Matacz (MDPI AG, 2021)
The article deals with the problematic heritage associated with the system of Nazi German underground air raid shelters currently located within the Polish state, in the Baltic port city of Szczecin. The unwanted heritage has been inventoried, archival materials collected, and comparative analyses made of ways in which the underground space can be revitalised. An attempt was made to develop a typology of existing shelters and their locations. In order to overcome the negative associations with the warlike military space, positive system solutions were sought for the productive use of existing concrete structures located underground in central, easily accessible areas of the city districts. A process of upcycling the space was used to make ecologically efficient use of the material resources contained in the shelters. In order to activate the local community, a modular, hydroponic plant-growing system, adapted to the prefabricated spaces of the historical air raid shelters, was proposed. In this way, the central location of the underground structures within the boundaries of residential neighbourhoods was exploited. Such action strengthens the food sovereignty of the inhabitants, initiates bottom-up activity within the boundaries of the neighbourhood unit, and builds social ties in the spirit of a regenerative economy and positive sustainability.